Acquisition of epithelial-mesenchymal transition phenotype in the tamoxifen-resistant breast cancer cell: a new role for G protein-coupled estrogen receptor in mediating tamoxifen resistance through cancer-associated fibroblast-derived fibronectin and β1-integrin signaling pathway in tumor cells. Issue 1 (December 2015) - Yuan, Jie; Liu, Manran; Yang, Li; Tu, Gang; Zhu, Qing; Chen, Maoshan; Cheng, Hong; Luo, Haojun; Fu, Weijie; Li, Zhenhua; Yang, Guanglun
Abstract Introduction Acquired tamoxifen resistance remains the major obstacle to breast cancer endocrine therapy. β1-integrin was identified as one of the target genes of G protein-coupled estrogen receptor (GPER), a novel estrogen receptor recognized as an initiator of tamoxifen resistance. Here, we investigated the role of β1-integrin in GPER-mediated tamoxifen resistance in breast cancer. Methods The expression of β1-integrin and biomarkers of epithelial-mesenchymal transition were evaluated immunohistochemically in 53 specimens of metastases and paired primary tumors. The function of β1-integrin was investigated in tamoxifen-resistant (MCF-7R) subclones, derived from parental MCF-7 cells, and MCF-7R β1-integrin-silenced subclones in MTT and Transwell assays. Involved signaling pathways were identified using specific inhibitors and Western blotting analysis. Results GPER, β1-integrin and mesenchymal biomarkers (vimentin and fibronectin) expression in metastases increased compared to the corresponding primary tumors; a close expression pattern of β1-integrin and GPER were in metastases. Increased β1-integrin expression was also confirmed in MCF-7R cells compared with MCF-7 cells. This upregulation of β1-integrin was induced by agonists of GPER and blocked by both antagonist and knockdown of it in MCF-7R cells. Moreover, the epidermal growth factor receptor/extracellular regulated protein kinase (EGFR/ERK) signaling pathway was involved in this transcriptional regulation since specific inhibitors of these kinases also reduced the GPER-induced upregulation of β1-integrin. Interestingly, silencing of β1-integrin partially rescued the sensitivity of MCF-7R cells to tamoxifen and the α5β1-integrin subunit is probably responsible for this phenomenon. Importantly, the cell migration and epithelial-mesenchymal transition induced by cancer-associated fibroblasts, or the product of cancer-associated fibroblasts, fibronectin, were reduced by knockdown of β1-integrin in MCF-7R cells. In addition, the downstream kinases of β1-integrin including focal adhesion kinase, Src and AKT were activated in MCF-7R cells and may be involved in the interaction between cancer cells and cancer-associated fibroblasts. Conclusions GPER/EGFR/ERK signaling upregulates β1-integrin expression and activates downstream kinases, which contributes to cancer-associated fibroblast-induced cell migration and epithelial-mesenchymal transition, in MCF-7R cells. GPER probably contributes to tamoxifen resistance via interaction with the tumor microenvironment in a β1-integrin-dependent pattern. Thus, β1-integrin may be a potential target to improve anti-hormone therapy responses in breast cancer patients.